Analisis Peramalan Jumlah Penjualan Susu pada PT. Superindo Utama Jaya Menggunakan Metode Weighted Moving Average - Septianingrum, Nesyya; Saprudin, Usep (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to implement the Weighted Moving Average method for forecasting milk sales at PT. Superindo Utama Jaya. Data were collected through field observations, covering sales from January to December 2023. The research applies time series analysis and the Weighted Moving Average method to forecast sales from July 2023 to July 2024, with the following results: 4,822.95; 4,871.57; 4,973.04; 5,151.90; 5,385.71; 5,420.04; 5,020.85; 5,203.76; 5,181.46; 5,151.71; 5,127.70; 5,128.26; 5,142.26. The Mean Absolute Error (MAE) and Mean Squared Error (MSE) were calculated, resulting in an MAE of 0.021% and an MSE of 209,932.99.